2010
DOI: 10.1519/jsc.0b013e3181d75806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preload 4 Repetition Maximum on 100-m Sprint Times in Collegiate Women

Abstract: The purpose of this study was to determine the effects of postactivation potentiation (PAP) on track-sprint performance after a preload set of 4 repetition maximum (4RM) parallel back half-squat exercises in collegiate women. All subjects (n = 12) participated in 2 testing sessions over a 3-week period. During the first testing session, subjects performed the Controlled protocol consisting of a 4-minute standardized warm-up, followed by a 4-minute active rest, a 100-m track sprint, a second 4-minute active res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 21 publications
3
55
0
1
Order By: Relevance
“…Most studies found in the current review suggest the presence of post-activation potentiation in different athletics events 16,34,35,36,37,38,39 . This may be associated with neuromuscular and molecular changes induced by strength and power activities such as: 1) better recruitment of motor units, especially type-IIx motor units, which have a higher contraction velocity and capacity to generate tension; 2) increased availability of Ca ++ for contraction and 3) increased phosphorylation of light myosin chains, facilitating the interaction of contractile filaments 1,3 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Most studies found in the current review suggest the presence of post-activation potentiation in different athletics events 16,34,35,36,37,38,39 . This may be associated with neuromuscular and molecular changes induced by strength and power activities such as: 1) better recruitment of motor units, especially type-IIx motor units, which have a higher contraction velocity and capacity to generate tension; 2) increased availability of Ca ++ for contraction and 3) increased phosphorylation of light myosin chains, facilitating the interaction of contractile filaments 1,3 .…”
Section: Discussionmentioning
confidence: 78%
“…The results showed higher CMJ height after performing squatting compared to control situation (p = 0.01). Linder et al 39 investigated the effect of a series of 4RMs on squatting on the 10-meter running speed in 12 young females and the results indicated improvement of 0.19 seconds (1.2%) in the running time nine minutes after the squatting protocol (Pre = 17.14 ± 1.55, Post = 16.95 ± 1.55). Evetovich et al 36 found an increase in vertical jump height (Pre = 61.9 ± 12.3 cm; Post = 63.6 ± 11.6 cm) and horizontal jump distance (Pre = 93.7 ± 11.0 cm; Post = 95.9 ± 11.5 cm) eight minutes after three squat series at 85% 1RM squats in Athletic university athletes of both sexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most of the PAP studies have been based on jumping, only a few studies have investigated the effects on sport-specific performance (Mcbride et al, 2005;Paff, 1997). These studies have been reported to improve dynamic performance in competitive sports such as cycling and sprinting (Chatzopoulos et al, 2007;Hamada et al, 2000;Linder et al, 2010;Mcbride et al, 2005). In a study of Chatzopoulos et al (2007) conducted, it was reported that for amateurs, 90% of 1 TM increased the effect of PAP on short distances of 10 and 30 meters after 10-time repetitions of single foot squat.…”
Section: Introductionmentioning
confidence: 99%
“…In the KSJ group, four to six repetitions of kettlebell swings were performed followed by five consecutive countermovement squat jumps. A recovery period of 3 min between the resistance training exercise (squats/ kettlebell swings) and the plyometric exercise (countermovement squat jumps) was provided to allow for phosphocreatine resynthesis [7,9,19,20] (Figure 4).…”
mentioning
confidence: 99%